2013
DOI: 10.1213/ane.0b013e3182a0d7a7
|View full text |Cite
|
Sign up to set email alerts
|

A Matter of Life or Limb? A Review of Traumatic Injury Patterns and Anesthesia Techniques for Disaster Relief After Major Earthquakes

Abstract: Based on this analysis, early disaster surgical intervention will focus on surviving patients with limb injury. All anesthetic techniques have been safely used for medical relief. While regional anesthesia may be an intuitive choice based on these findings, in the context of collapsed medical infrastructure, provider experience may dictate the available anesthetic techniques for earthquake survivors requiring urgent surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(41 citation statements)
references
References 33 publications
2
37
1
1
Order By: Relevance
“…The results from previous studies showed that a majority of earthquake injuries were musculoskeletal,8, 9, 10, 11 whereas in the present study, non-musculoskeletal injuries were higher within 24 h than after 24 h (67% vs. 53%, respectively); however, this was not statistically significant. The ISS, presence of multiple injuries and presence of crush syndrome were significantly higher within 24 h, which indicates that patients with more severe injuries tend to present earlier.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…The results from previous studies showed that a majority of earthquake injuries were musculoskeletal,8, 9, 10, 11 whereas in the present study, non-musculoskeletal injuries were higher within 24 h than after 24 h (67% vs. 53%, respectively); however, this was not statistically significant. The ISS, presence of multiple injuries and presence of crush syndrome were significantly higher within 24 h, which indicates that patients with more severe injuries tend to present earlier.…”
Section: Discussioncontrasting
confidence: 91%
“…Instead, almost all studies reported that a majority of patients who reached a hospital had either musculoskeletal injuries or non-serious vital organ injuries. Mortality in such patients was not very high 6, 7, 8, 9, 10, 11. No study has yet addressed the following question: is there any difference in the pattern and severity of injuries in relation to the timing of admission in a hospital?…”
Section: Introductionmentioning
confidence: 99%
“…When urgent surgical intervention is required and an anesthesiologist is unavailable, the use of regional anesthetics should be considered. 23 Even with limited resources in disaster situations, a general physician can provide effective treatment, referring only specific patients to a subspecialist for treatment. 18 Tetanus is an acute, often fatal disease caused by wound contamination with Clostridium tetani.…”
Section: Discussionmentioning
confidence: 99%
“…However, anaesthetic treatment in a field hospital setting has only been reported as part of intraoperative management 9. Our vision that PSA should be a part of paediatric emergency care after a disaster was based on previous experience with four field hospitals deployed in Armenia, Turkey, India and Haiti 10…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on anaesthesia practices in the setting of a field hospital reported that ketamine was the most commonly prescribed medication 9. We used ketamine in 8 out of 10 children due to its high safety profile 11…”
Section: Discussionmentioning
confidence: 99%